What is quantitative longitudinal data analysis - Gayle,Vernon; Lambert,Paul (London Bloomsbury Academic, 2018)
"Across the social sciences, there is widespread agreement that quantitative longitudinal research designs offer analysts powerful scientific data resources. But, to date, most texts on social survey analysis have been written from a statistical, rather than a social science data analysis perspective and they lack adequate coverage of common practical challenges. This book aims to provide a practical and up-to-date introduction to influential approaches to quantitative longitudinal data analysis in the social sciences. The book will discuss definitions and terms, explain the relative attractions of such a design and enumerate in an accessible way the main techniques of analysis, explaining their requirements, statistical properties and their substantive contribution. The book is designed for postgraduates and researchers across the social sciences considering the use of quantitative longitudinal data resources in their research. It will also be an excellent text for undergraduate and postgraduate courses on advanced quantitative methods."--Bloomsbury Publishing
Introduction to quantitative longitudinal data. -- Quantitative longitudinal datasets. -- Temporal analysis with cross-sectional data. -- The analysis of duration data. -- The analysis of repeated contacts data. -- Adopting the long view: A review of analytical methods
Includes bibliographical references and index
Keywords: Social sciences -- Statistical methods; Social sciences -- Longitudinal studies; Longitudinal method